Spin Parity of Spiral Galaxies. I. Corroborative Evidence for Trailing Spirals - Iye, Masanori; Tadaki, Ken-ichi; Fukumoto, Hideya (The Astrophysical journal, 2019)
Whether the spiral structure of galaxies is trailing or leading has been a subject of debate. We present a new spin parity catalog of 146 spiral galaxies that lists the following three pieces of information: whether the spiral structure observed on the sky is S-wise or Z-wise; which side of the minor axis of the galaxy is darker and redder, based on examination of Pan-STARRS and/or ESO/DSS2 red image archives; and which side of the major axis of the galaxy is approaching us based on the published literature. This paper confirms that all of the spiral galaxies in the catalog show a consistent relationship among these three parameters, without any confirmed counterexamples, which supports the generally accepted interpretation that all the spiral galaxies are trailing and that the darker/redder side of the galactic disk is closer to us. Although the results of this paper may not be surprising, they provide a rationale for analyzing the S/Z winding distribution of spiral galaxies, using the large and uniform image databases available now and in the near future, to study the spin vorticity distribution of galaxies in order to constrain the formation scenarios of galaxies and the large-scale structure of the universe.